It's Not That Great Anymore: The Central Role of Defense Mechanisms in Grandiose and Vulnerable Narcissism - Kampe, Leonie; Bohn, Johannes; Remmers, Carina; Hörz-Sagstetter, Susanne (Frontiers in Psychiatry, 2021)
Objectives. The concept of narcissism contains a yet unresolved paradox: Its grandiose facet depicts the psychopathological core but is often associated with life-satisfaction and overall functioning, whereas its vulnerable facet is associated with psychological distress, but still not included in the international classification systems. Our goal was to investigate the relationship between the two facets of narcissism expecting underlying defense mechanisms to be core elements. First, we aimed to identify defense mechanisms specific to grandiose and vulnerable narcissism. Second, we explored how both facets are differentially associated with psychological distress, assuming that grandiose narcissism would be associated with less psychological distress than vulnerable narcissism. Third, we investigated the mediating role of defense mechanisms between narcissism and psychological distress. Methods. In a non-clinical sample of N=254 individuals, the Pathological Narcissism Inventory was used for the assessment of grandiose and vulnerable facets of narcissism, the Defence Style Questionnaire for defense mechanisms, and the Brief Symptom Inventory for psychological distress. Structural equation modeling was employed to identify distinct factors of grandiose and vulnerable narcissism. Associations between specific defense mechanisms and both facets were calculated. Furthermore, the direct association between both facets and psychological distress was examined. We finally explored whether defense mechanisms mediate the association between distress and both grandiose and vulnerable narcissism. Results. A distinct pattern of defense mechanisms for each facet of narcissism could be extracted: Both facets showed significant positive correlations with specific intermediate and all maladaptive defense mechanisms. Only grandiose narcissism showed significant positive correlations with adaptive defenses. Vulnerable narcissism showed negative correlations with all adaptive defenses. Specifically, grandiose narcissism was significantly related to anticipation, pseudo-altruism, rationalization, and dissociation, whereas vulnerable narcissism was negatively related to all these defense mechanisms. While grandiose narcissism was not related to psychological distress, vulnerable narcissism showed high correlations with psychological distress. Intriguingly, mediator analysis found that grandiose narcissism was related to psychological distress when mediated by maladaptive defense mechanisms. Discussion. The role of defense mechanisms is central for a differentiated understanding of the many faces of narcissism. The relevance of assessing defense mechanisms in clinical settings, and related empirical findings are discussed.